Hydrophobic Alumina Coatings for Magnesium Substrates with Advancing Electromagnetic Wave Absorption Capability - Zhang, Fangfang; Zuo, Yuanyuan; Wu, Degang; Yang, Guanda; Schubert, Dirk W.; Nie, Lin (Journal of Materials Engineering and Performance, 2024)
This study explores the surface modifications and properties of magnesium substrates through the application of alumina coatings for improved functionalities. Surface microstructures were investigated using a field emission scanning electron microscope after roughening treatments and alumina spray coatings. Elemental mapping revealed the distribution of coatings, demonstrating successful modifications with silane coupling agent and uniform alumina distribution. Contact angle measurements showcased enhanced hydrophobicity post-alumina coating, with notable improvements in contact angles over various liquids and self-cleaning assessments. Furthermore, wear resistance tests indicated the durability of the alumina coatings, displaying high stability even after repeated abrasions with sandpaper. The self-cleaning tests unveiled the remarkable performance of alumina-coated surfaces in repelling contaminants, underscoring their effective self-cleaning characteristics. Furthermore, the electromagnetic wave absorption properties of magnesium substrates coated with alumina demonstrated outstanding absorption efficiency, notably within the 7-11 GHz frequency range. This comprehensive analysis highlights the potential and effectiveness of alumina coatings in enhancing the properties of magnesium sheets, specifically in improving hydrophobicity, wear resistance, self-cleaning capabilities, and electromagnetic wave absorption.
CRIS-Team Scopus Importer:2024-08-09
Keywords: alumina coatings; electromagnetic wave absorption; hydrophobicity; magnesium substrate; wear resistance